The answer to that question is B.
Answer:
f(-1) = 0
f(2) = 16
Step-by-step explanation:
f(-1) = 4(-1) + 4 = 0
f(2) = 4(2) + 8 = 16
Answer:
[y]=-18 so y belongs to (-18,-17)
Step-by-step explanation:
Answer:
20. 3
Step-by-step explanation:
23.6 - 2 × 3 ÷ 2 = 23.6 - 3
= 20.3
Answer:
Option D.
Step-by-step explanation:
we know that
The compound interest formula is equal to
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
in this problem we have
substitute in the formula above